2013
DOI: 10.4067/s0718-58392013000200015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on boron adsorption in some soils of Paraná, Brazil

Abstract: Temporary B deficiency can be triggered by liming of acid soils because of increased B adsorption at higher soil pH. Plants respond directly to the activity of B in soil solution and only indirectly to B adsorbed on soil constituents. Because the range between deficient and toxic B concentration is relatively narrow, this poses difficulty in maintaining appropriate B levels in soil solution. Thus, knowledge of the chemical behavior of B in the soil is particularly important. The present study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
(42 reference statements)
3
10
0
1
Order By: Relevance
“…According to the highest "r 2 " values, Langmuir isotherm model seemed to be the most efficient model fitting the sorption of B on soils and clay minerals. The values obtained herein were comparable to those recorded by Steiner and Lana (2013) who found that the "a" value ranged from 0.2 to 1.7 L mg g -1 ,while the b value ranged from 0.004 to 0.049L g -1 soil. This indicates that sorption of B took place in monolayers (Tan.…”
Section: Sorption Of B On Soils and Their Separated Clay Fractions Vesupporting
confidence: 90%
See 1 more Smart Citation
“…According to the highest "r 2 " values, Langmuir isotherm model seemed to be the most efficient model fitting the sorption of B on soils and clay minerals. The values obtained herein were comparable to those recorded by Steiner and Lana (2013) who found that the "a" value ranged from 0.2 to 1.7 L mg g -1 ,while the b value ranged from 0.004 to 0.049L g -1 soil. This indicates that sorption of B took place in monolayers (Tan.…”
Section: Sorption Of B On Soils and Their Separated Clay Fractions Vesupporting
confidence: 90%
“…It is worthy to mention that the maximum monolayer adsorption capacity ("a" values) increased with increasing the pH of the metalloid soil or clay fraction suspension from 5 to 9 by 1.3, 2.3, 1.5 and 2.5 fold for the clayey soil, calcareous soil, clay fraction separated from the non-calcareous soil, clay fraction separated from the calcareous soil, respectively. In the calcareous soil, the affinity constant seemed to decrease with increasing the pH of the suspension and this result is confirmed by the findings of Steiner and Lana (2013) who recorded that the bonding energy of the B-sorption on soils decreased with increasing the pH of the aqueous solution. On the other hand, this constant seemed to increase in both the soil and on the clay fraction separated from the calcareous soil with increasing the pH of the suspensions.…”
Section: Sorption Of B On Soils and Their Separated Clay Fractions Vesupporting
confidence: 76%
“…In the present study, adsorption isotherms were not performed, which could show the maximum capacity of B adsorption (MCBA) by the soil. In some soils from Paraná state, Brazil, which are very similar to the soil used in the present study, MCBA is up to 50 mg kg -1 (Steiner and Lana, 2013), but in some soils from São Paulo state, however, MCBA is only 11 mg kg -1 (Alleoni and Camargo, 2000). At the highest rate applied in this study (100 mg kg -1 B), even considering that B was mixed with only 60 % of the soil volume of each column, the amount added would be larger than the MCBA, and even so, less than 30 % of the applied B was leached (Table 1).…”
Section: Resultssupporting
confidence: 55%
“…This behavior is similar to the chemical adsorption of cations in the soil. In addition to acidity, some other soil attributes also affect the sorption of B, including mineralogical composition (Alleoni and Camargo, 2000;Azevedo et al, 2001;Soares et al, 2008), texture (Alleoni and Camargo, 2000;Saltali et al, 2005) and the organic matter content (Azevedo et al, 2001;Soares et al, 2008), with consequences on the concentration of B in the soil solution (Steiner and Lana, 2013;Szulk and Rutkowska, 2013). Thus, leaching of B is higher from sandy soils than from clayey soils, especially in regions with high average annual rainfall (Silva et al, 1995;Communar and Keren, 2006), where B may reach the subsoil within a short period of time (Silva et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and boron deficiency can occur in very weathered soils due to continuous cropping, soil erosion, leaching of exchangeable bases, reduction of soil organic matter, and adsorption by aluminum and iron (hydr)oxides LANA, 2013;LANA et al, 2013). Boron plays a key role in root function and low B levels reduce the plant's ability to uptake water and nutrients from the soil, which often induces a Ca deficiency (TARIQ;MOTE, 2007).…”
Section: Introductionmentioning
confidence: 99%